2017
DOI: 10.11591/ijece.v7i3.pp1219-1227
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative study on Handoff Algorithms for GSM and CDMA Cellular Networks

Abstract: The GSM, CDMA cellular systems are most trendy 2G and 3G digital cellular telecommunications systems, which is widely used throughout the world. These systems have many advantages such as high security, higher quality of call transmission over the long distances, low transmitted power, and enhanced capacity with more efficient utilization of the frequency spectrum. With these advantages these cellular systems have attracted more subscribers with more attention in the field of mobile communications. One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…Telekomunikasi adalah teknik pengiriman atau penyampaian informasi dari suatu tempat ke tempat lain, sedangkan sebuah sistem telekomunikasi selular adalah komunikasi antar pesawat di mana salah satu pesawat bergerak atau berpindah lokasi dengan menggunakan sistem komunikasi tanpa kabel (wireless) [1] [2] [3] [4]. Teknologi telekomunikasi merupakan salah satu teknologi yang berkembang dengan sangat cepat, dimulai dengan layanan 1G sampai dengan 4G seperti yang ditunjukkan pada gambar 1. dan tabel 1 [3] [4] [5].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Telekomunikasi adalah teknik pengiriman atau penyampaian informasi dari suatu tempat ke tempat lain, sedangkan sebuah sistem telekomunikasi selular adalah komunikasi antar pesawat di mana salah satu pesawat bergerak atau berpindah lokasi dengan menggunakan sistem komunikasi tanpa kabel (wireless) [1] [2] [3] [4]. Teknologi telekomunikasi merupakan salah satu teknologi yang berkembang dengan sangat cepat, dimulai dengan layanan 1G sampai dengan 4G seperti yang ditunjukkan pada gambar 1. dan tabel 1 [3] [4] [5].…”
Section: Pendahuluanunclassified
“…Fasilitas kordinasi seluruh frekuensi melalui base-station base station. Sistem CDMA menyediakan soft hand-off dari satu base-station ke base-station lainnya sebagai sebuah roaming telepon bergrak dari sel ke sel, melakukan soft handoff dikarenakan semua sistem menggunakan frekuensi yang sama [1]. Fungsi spread-spectrum dan kekuatan kendali yang memperbesar kapasitas panggil CDMA mengakibatkan bandwith yang cukup untuk bermacam-macam layanan data multimedia, dan skema soft hand-off menjamin: Tidak hilangnya data, meningkatkan kualitas suara, memperbaiki karakteristik cakupan yang dapat menurunkan jumlah sel, meningkatkan privacy dan security, menyederhanakan perencanaan sistem, memerlukan daya pancar yang lebih rendah, sehingga waktu bicara ponsel dapat lebih lama, mengurangi interferensi pada sistem lain, lebih tahan terhadap multipath, dapat dioperasikan bersamaan dengan teknologi lain (misal AMPS (Advanced Mobile Phone Service)).…”
Section: Hasil Dan Pembahasanunclassified
“…In the literature, most of the handoff algorithms are designed between similar networks which are based on Received Signal Strength (RSS) e.g GSM to GSM or CDMA to CDMA [4,5]. Various vertical handoff algorithms are observed and designed based on area of application and user requirements [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ruippo et al [28] have presented a study that emphasize on developing an oscillator that is controlled by voltage with highly less amount of phase noises operating at critical frequencies of GSM signals. Neeraja and Rao [29] have presented the comparative research for CDMA and GSM cellular networks over Handoff algorithm and the research is found helpful in improving cellular service. In Xie et al [30] explained the data transmission mechanism based on the measurement acquired from railway based GSM, i.e., GSM-R and concluded that this work could be considered for theoretical researches.…”
Section: Introductionmentioning
confidence: 99%